2019
DOI: 10.3389/fpsyg.2019.00632
|View full text |Cite
|
Sign up to set email alerts
|

An Eye-Tracking Study of Statistical Reasoning With Tree Diagrams and 2 × 2 Tables

Abstract: Changing the information format from probabilities into frequencies as well as employing appropriate visualizations such as tree diagrams or 2 × 2 tables are important tools that can facilitate people’s statistical reasoning. Previous studies have shown that despite their widespread use in statistical textbooks, both of those visualization types are only of restricted help when they are provided with probabilities, but that they can foster insight when presented with frequencies instead. In the present study, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(43 citation statements)
references
References 87 publications
(145 reference statements)
5
38
0
Order By: Relevance
“…Thus, the pre-Bayes strategy is highly dependent on the Bayesian situation and the concrete frequencies in this situation. This is apparent also in the results of Bruckmaier et al (2019), who used two situations with h 1 /(d 1 + d 3 ) > 1 and, accordingly, found nearly no pre-Bayes strategy. In our study, we used situations with h 1 /(d 1 + d 3 ) > 1, and situations with Zhu and Gigerenzer (2006), we expect few answers representing the pre-Bayes strategy in the first case.…”
Section: Hypothesesmentioning
confidence: 80%
See 4 more Smart Citations
“…Thus, the pre-Bayes strategy is highly dependent on the Bayesian situation and the concrete frequencies in this situation. This is apparent also in the results of Bruckmaier et al (2019), who used two situations with h 1 /(d 1 + d 3 ) > 1 and, accordingly, found nearly no pre-Bayes strategy. In our study, we used situations with h 1 /(d 1 + d 3 ) > 1, and situations with Zhu and Gigerenzer (2006), we expect few answers representing the pre-Bayes strategy in the first case.…”
Section: Hypothesesmentioning
confidence: 80%
“…Since the study was based on an eye-tracking method, the study included a very small sample size of 24 students. Bruckmaier et al (2019) found only strategies discussed so far for the students' Bayesian reasoning to be supported by natural frequencies and a tree diagram or 2 × 2table. The findings concerning the tree diagram supported the hypothesis that the hierarchy of the tree diagram triggers people to identify a subset-set relation in different levels of the tree.…”
Section: Strategies In Bayesian Situationsmentioning
confidence: 87%
See 3 more Smart Citations